THE LANGUAGE OF ALTERNATE UNIVERSE OF ROMANCE: A MULTIMODAL DISCOURSE ANALYSIS ON BTS’ FAN ARTS - Eva Leiliyanti; Diyantari Diyantari; Marsha Mayra (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
Shipping allows fans to build a perfect self and relationship. From several types of shipping, this multimodal discourse analysis concentrates on the queer reading of BTS fans’ slash shipping, i.e. the shipping that focuses on a male-male relationship (heterosexual romantic relationship of the members is a taboo, as the fans position the members as their collective boyfriends) in the form of comic strips. Through continuously producing fan art (in this case, the comic), the fans promote the artists to other fans around the world. This study focused on BTS, a K-Pop boy group, whose popularity has contributed to the high number of South Korean tourism. The data source, five comics, were selected from Twitter and Instagram accounts of BTS’ fans in 2020 by employing stratified purposeful sampling. The data are the visual and written texts from the 5 comics. The language evaluation theory developed by Martin and White along with Kress and van Leeuwen’s social semiotics and Judith Butler’s performativity was deployed to unravel the fans’ romantic textual illusion towards the group. The findings demonstrate that the fans construct the members into seme/uke gender attribution both physically and psychologically in homonormative based stories.